Equine Sesamoiditis: Report on one case - DIAKAKIS (Ν.ΔΙΑΚΑΚΗΣ) N.; MARAKI (M. MAPAKH), M.; PATSIKAS (Μ. ΠΑΤΣΙΚΑΣ) M.; DESIRIS (Α. ΔΕΣΙΡΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Sesamoiditis is the inflammation of the proximal sesamoid bones. The aetiopathogenesis of sesamoiditis is still open to discussion, while several therapeutic protocols have been put forward. This study presents the case of a l6year-old Dutch Warmblood gelding with sesamoiditis of the right forelimb. A right forelimb lameness (3/10), with a positive lower limb flexion test (5/10) was noted, and enlargement of the soft tissues of the right fore fedock. Based on the positive low four point nerve block, radiographic examination of the fedock revealed the presence of numerous radiolucent areas along the palmar aspect of the sesamoidean bones, but only minimal new bone formation on its base. An ultrasonographic evaluation of the suspensory ligament and the distal sesamoidean ligaments was made, something which did not detect any abnormalities. Phenylobutazone (4mg/kg i.v. SID) was administered for five days and, also, local hydrotherapy with cold water was used and the horse was given a 15- day box rest. The horse was re-examined three months following the initial inspection. The radiographic examination of the fetlock showed the same lesions with the initial examination. The second ultrasonographic evaluation, though, showed enlargement by 50% of the lateral branch of the suspensory ligament with loss of the normal outline. Moreover, anechoic areas were noted within the branch with calcification at its insertion site. To address the inflammation phenylobutazone (4mg/kg i.v.) was administered for ten days and, also, local hydrotherapy with cold water was used. Box-rest for 30 days was recommended. In the end of this period there was no inflammation in the fetlock region. A blister (TWYDIL liquid blister®) was used in order to resolve the chronic inflammation of the suspensory apparatus. The horse was then given three weeks of box rest and received correcting shoeing (egg- bar shoe with elevated heels and rolled- toe). It was then put in a gradually increasingexercise program.